A systematic review of self-neglect and its risk factors among community-dwelling older adults. (2nd December 2021) - Yu, Mingming; Gu, Libin; Shi, Yuexian; Wang, Wenru
Abstract: Objectives: To systematically review published evidence on self-neglect (SN) and its risk factors among community-dwelling older adults. Method: A comprehensive literature search was conducted in PubMed, Embase, CINAHL Plus, PsycINFO, and Scopus for studies that were published in English from inception to 8 April 2020. Grey database was also included to ensure a thorough search. The study quality was assessed by two reviewers independently using the Newcastle-Ottawa Scale or the checklist suggested by the Agency for Healthcare Research and Quality. Results: A total of 19 studies was included in this review. Various tools were used to assess SN among the available studies. The prevalence rates of SN among community-dwelling older adults ranged from 18.4% to 29.1%. The risk factors of SN identified by these studies involved sociodemographic characteristics (male gender, older age, low economic status, ethnicity, lower educational level, marital status, and lower number of children), health-related characteristics (cognitive impairment, lower level of physical function, nutritional status, higher number of medical comorbidities, and pain), psychological characteristics (depression), and social context characteristics (living alone, lower social networks and social engagement, lower neighborhood cohesion, and neighborhood disorder). Conclusion: SN is a common and under-recognized phenomenon among community-dwelling older adults. Our review provides healthcare professionals with an insight into SN and its risk factors. More studies are required to test the potency of each independent risk factor to deepen our understanding of this particular phenomenon.